Comparative study of chromium stress in pot-cultured wheat and rice seedlings: role of DTPA and EDTA chelation in bioaccumulation and antioxidant responses: Chelator-mediated chromium stress response - Sarangi, Ansul; Das, Manoja; Behera, Kambaska Kumar; Samal, Nibedita (ORYZA-An International Journal of Rice, 2025)
Chromium (Cr+6) is a highly toxic heavy metal that adversely affects plant growth and physiology. This study aimed to evaluate the effects of Cr+6 stress on biomass accumulation, metal bioaccumulation, and antioxidant defense responses in 20-day-old wheat (Triticum aestivum L. cv. HD-2894) and rice (Oryza sativa L. cv. Sabita) seedlings grown under pot culture conditions. Seedlings were exposed to increasing Cr concentrations (20-80 mg L-¹), with or without chelating agents diethylenetriaminepentaacetic acid (DTPA) and ethylenediaminetetraacetic acid (EDTA) at 20 mg L-¹. Chromium exposure significantly reduced shoot and root biomass in a dose-dependent manner, with wheat showing up to 54.8% and 51.6% reductions in shoot and root biomass, respectively, and rice exhibiting reductions of 29.8% and 47.8%. Cr accumulation was higher in roots than shoots, suggesting limited translocation. Chelator application notably enhanced growth and reduced shoot Cr accumulation. DTPA and EDTA improved shoot biomass by up to 154% (wheat) and 37.2% (rice), and reduced Cr content in shoots by 11-31%. Bioconcentration factor (BCF) and total accumulation rate (TAR) increased under chelator treatments, while transportation index (Ti) was moderated, indicating greater root retention of Cr. Antioxidant enzymes-peroxidase (POX), catalase (CAT), and superoxide dismutase (SOD) were significantly upregulated under Cr stress, with the highest fold increases observed in root tissues. Combined Cr + EDTA (T12) and Cr + DTPA (T8) treatments led to maximum antioxidant activation, suggesting enhanced oxidative stress tolerance. Overall, the study demonstrates that Cr+6 impairs plant biomass and induces oxidative damage, while DTPA and EDTA alleviate toxicity through reduced metal bioavailability and stimulation of antioxidant defenses. EDTA was slightly more effective than DTPA, highlighting its potential in phytoremediation strategies for Cr-contaminated soils.